The National War Labor Board: Stability, Social Justice, and the Voluntary State in World War I - Schatz, Ronald W. (Labour / Le Travail, 1986)
This article reviews the book, "The National War Labor Board: Stability, Social Justice, and the Voluntary State in World War I," by Valeric Jean Conner.